2014
DOI: 10.1186/1471-2164-15-137
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in bovine adipogenesis: genomic context, expression and function

Abstract: BackgroundMicroRNAs (miRNAs) are small non-coding RNAs found to regulate several biological processes including adipogenesis. Understanding adipose tissue regulation is critical for beef cattle as fat is an important determinant of beef quality and nutrient value. This study analyzed the association between genomic context characteristics of miRNAs with their expression and function in bovine adipose tissue. Twenty-four subcutaneous adipose tissue biopsies were obtained from eight British-continental crossbred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 74 publications
1
47
0
2
Order By: Relevance
“…In contrast, the plasma samples were enriched with moderate concentrations of miRNAs associated with adipose tissue, such as miR-15a, miR-19a/b, miR-21, miR-27b, miR-92a/b, miR-103, miR-106a/b, miR-107, miR-125b, and miR-150 [11,12]. It is especially notable that the bovine-specific miR-1584-5p, miR-2305, miR-2412, and miR-2478, most of which are associated with energy metabolism [32], were highly enriched in the plasma samples of both groups in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the plasma samples were enriched with moderate concentrations of miRNAs associated with adipose tissue, such as miR-15a, miR-19a/b, miR-21, miR-27b, miR-92a/b, miR-103, miR-106a/b, miR-107, miR-125b, and miR-150 [11,12]. It is especially notable that the bovine-specific miR-1584-5p, miR-2305, miR-2412, and miR-2478, most of which are associated with energy metabolism [32], were highly enriched in the plasma samples of both groups in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated that miRNAs play crucial roles in various biological and physiological processes [4][5][6][7][8][9]. Including adipocyte differentiation and adipogenesis [10][11][12]. Some miRNAs enhance adipogenesis [13][14][15][16], whereas others exert negative effects by targeting essential adipogenic genes directly [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…From these findings, it could be inferred that the induction of miR-17-5p in vivo might manipulate the cellular environment such that it favors FMDV replication, while miR-1281 is down-regulated due to an antagonistic effect. Given that miR-1281 mimics impede FMDV replication and the reported role of miR-1281 in cattle [50], it seems that the state of lipid homeostasis in the host plays an important role in the outcome of FMDV infection regardless of whether it is acute or persistent. A survey of all the predicted target genes of these two miRNAs using multiple online algorithms failed to produce a consensus target to be explored in this current study (see Additional file 2: Table S1).…”
Section: Discussionmentioning
confidence: 99%